The translation of al Fi'l al Madi in Muhammad Ibn 'Abd al Wahhab's al Usus al Salasah into 'the three fundamental principles" - Khairun Nisa (Faculty of Adab and Cultural Sciences State Islamic University Sunan Kalijaga, 2015)
st,1/ws.c.1